Gene G. answered • 06/09/13

You can do it! I'll show you how.

y varies inversely with the square of x:

square of x is **x ^{2}**

Inverse of square of x is **1 / x ^{2}**

So the equation would be:

**y = k / x ^{2}**

where **k** is a proportionality constant.

To find the value of **k**, plug in the known values for x and y: x=3, y=45

**45 = k / 3 ^{2} = k / 9**

**k=405**

Now you have the full equation with proportionality factor.

**y = 405 / x ^{2}**

then, for x=5:

**y = 405 / 5 ^{2} = 405 / 25**

**y = 16.2**